Law Enforcement Against Illegal Orphanage Managers in Sexual Violence Against Foster Children - Bulan Cahya, Rut Erika; Marwinata, Pepy (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Illegal orphanages operating without permits often pose environmental risks that are vulnerable to various forms of abuse, including sexual violence against the children they are supposed to protect. This study examines the legal enforcement against illegal orphanage managers in Gubeng, Surabaya, who are suspected of being involved in sexual violence against foster children and child abduction, as well as regulations related to the establishment of social institutions. Using a normative legal approach and qualitative analysis methods, data was obtained through legal literature studies, court decisions, and case reports in the Surabaya area. The results of the study show that law enforcement efforts are still hampered by weak supervision, a lack of synergy between agencies such as the Ministry of Social Affairs, the Police, and the Social Services Agency, as well as legal loopholes that allow illegal orphanages to operate without adequate control. Obstacles in coordination also affect the process of proving cases, so that even though the Child Protection Law has established severe sanctions, its implementation in the field is often not optimal. These findings emphasize the need to strengthen the monitoring system, improve inter-agency cooperation, and strengthen commitment to law enforcement to prevent similar cases from recurring.